2000
DOI: 10.1046/j.1442-2042.2000.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 5‐hydroxytryptamine and the effect of a new serotonin receptor antagonist (sarpogrelate) on detrusor smooth muscle of streptozotocin‐induced diabetes mellitus in the rat *

Abstract: Background: We evaluated the changes in the response of detrusor muscle to 5-hydroxytryptamine (5-HT; serotonin) and its receptor mechanisms in pathologic bladder of diabetes mellitus rats. Methods: Eight-week-old male Wistar rats were given an intraperitoneal injection of streptozotocin (STZ, 60 mg/kg) in order to induce diabetes mellitus (4 weeks' duration). The bladder strips (10 ¥ 2 mm) were subjected to a tension of 1.0 g in organ baths for the measurements of isotonic contractile responses to 5-HT or rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 18 publications
1
23
1
Order By: Relevance
“…Sikorski et al [11] suggested that the diminished contraction responses of the diabetic rat aorta to 5-HT may have occurred as a result of reductions in 5-HT receptor-mediated responses of smooth muscle. On the other hand, increased contraction responses to 5-HT were reported in diabetic pig bladder smooth muscle [12] . In comparison to this, according to our results, we may speculate that there was no change in 5-HT receptor regulation of diabetic HCC, and that sensitivity of smooth muscle cells of corpus cavernosum to 5-HT was not altered due to diabetes in ED patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sikorski et al [11] suggested that the diminished contraction responses of the diabetic rat aorta to 5-HT may have occurred as a result of reductions in 5-HT receptor-mediated responses of smooth muscle. On the other hand, increased contraction responses to 5-HT were reported in diabetic pig bladder smooth muscle [12] . In comparison to this, according to our results, we may speculate that there was no change in 5-HT receptor regulation of diabetic HCC, and that sensitivity of smooth muscle cells of corpus cavernosum to 5-HT was not altered due to diabetes in ED patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to diabetes mellitus, alterations of 5-HT-induced contractions have been seen in several tissues, such as in rat bladder, and the rabbit carotid and renal artery [9,10] . Therefore, the aim of our study was to find answers to two questions: (1) Does 5-HT-induced contraction alter in diabetic HCC?…”
Section: Rho-kinase Enzyme-induced 5-ht Contractionmentioning
confidence: 99%
“…This response was inhibited by a selective 5-HT 2A antagonist. However, when this response was related to the muscle mass (which was increased in diabetic animals), no difference was found (Kodama and Takimoto, 2000).…”
Section: Peripheral Targetsmentioning
confidence: 91%
“…Contractions due to direct stimulation of 5-HT 2 receptors of smooth muscle cells of cat, rat (Cohen, 1990;Saxena et al, 1985;Kodama and Takimoto, 2000;, and human (Klarskov and Hørby-Petersen, 1986) bladders, have been reported. Activation of 5-HT 3 receptors causes contractions mediated by stimulation of the receptor located on excitatory neurons in the bladder PHARMACOLOGY OF THE LOWER URINARY TRACT of cats (Saxena et al, 1985), mice (Holt et al, 1986), guinea pigs (Messori et al, 1995), rabbits (Chen, 1990;Barras et al, 1996), pigs (Sellers et al, 2000), and humans (Corsi et al, 1991;Tonini et al, 1994).…”
Section: Peripheral Targetsmentioning
confidence: 99%
“…pBOO, bladder wall thickness tended to increase (15), and similar alterations might occur, at least in part, in this rat model. In the present study, 5-HT induced bladder contraction, as described in reports on rats, cats, dogs, and humans (6,(10)(11)(12)26). The contractile responses to 5-HT was significantly enhanced by pBOO, and expression of mRNA encoding the 5-HT 2A and 5-HT 2B receptors was increased in the detrusor muscle layer following pBOO.…”
Section: Discussionmentioning
confidence: 61%